High‐sensitivity cardiac troponin T as a predictor of acute Total occlusion in patients with non‐ST‐segment elevation acute coronary syndrome. Issue 2 (21st December 2018) - Baro, Rocío; Haseeb, Sohaib; Ordoñez, Santiago; Costabel, Juan P.
Abstract : Background: A large percentage of patients with non‐ST‐segment acute coronary syndrome (NSTE‐ACS) present with acute total occlusion (TO) of some major epicardial vessel that does not generate electrocardiographic changes. Ongoing research into the methods of accurately predicting acute TO have not yielded great success. Hypothesis: High‐sensitivity cardiac troponin T (hs‐cTnT) has a good predictive value for the presence of acute TO of the culprit artery in patients with NSTE‐ACS. Methods: A single‐center retrospective study of 1011 patients diagnosed with NSTE‐ACS who underwent coronary angiography and hs‐cTnT measured on admission. The predictive value of hs‐cTnT in the presence of acute TO was assessed by the area under the ROC curve. Results: The mean age of the population was 67.12 ± 13.18 and 74.1% were male. 7.3% of the patients presented with acute TO. The AUC for hs‐cTnT to predict acute TO was 0.95. A hs‐cTnT value of 1006 ng/L (71.8 fold of the URL) best predicted the presence of acute TO, with a sensitivity of 86% and specificity of 95% positive predictive value (PPV): 86% and negative predictive value (NPV): 94%. Conclusions: Hs‐cTnT was a good predictor of acute TO in patients with NSTE‐ACS. Hs‐cTnT values greater than 1006 ng/L were highly predictive of acute TO of a major coronary vessel.